FAKSI DAN KONFLIK POLITIK DALAM PARTAI POLITIK: PARTAI KEADILAN SEJAHTERA - Wahyuni, Hilda; Ayu, Rizqa Febry (Jurnal Politik Pemerintahan Dharma Praja, 2022)
The collapse of the new order became a reflection for political parties in strengthening and expanding their political power to appear on the surface as a democratic spirit that began to develop in Indonesia. This became an opportunity for the Partai Keadilan (PK) to compete by changing its name to the Partai Keadilan Sejahtera (PKS) and experiencing significant developments in the political scene in Indonesia. The developments experienced by PKS triggered conflict within the party itself. The factions that emerged in the PKS party created conflicts that made political parties lack electability and had an impact on vote acquisition during general elections. This research is a library research with a qualitative approach which finds that political conflict in PKS can occur due to three things, namely political conflict to occupy political positions, conflicts resulting from policies and conflicts of opinion on political institutions. Efforts to resolve conflicts in political parties are resolved by means of deliberation by the party consultative assembly, if this does not work, then it can then be processed through legal proceedings to the district court and cassation at the supreme court.